Unraveling the diversity of the flat wasp Pseudisobrachium Kieffer, 1904 (Hymenoptera: Bethylidae) from the Brazilian Amazon region - Gomes, Leonardo A.; Colombo, Wesley D.; Gobbi, Fernanda T.; Azevedo, Celso O.; Somavilla, Alexandre (Zootaxa, 2026)
In this study, 40 species of Pseudisobrachium Kieffer were recorded from the Brazilian Amazon region. Among them, four species, namely, P. brasiliense Kieffer, P. crassicornis (Westwood), P. inchoatum Kieffer, and P. rufopictum (Kieffer) had already been recorded from the region, but their known distributions were expanded with new occurrence records. Two additional species are reported from Brazil for the first time: P. angulatum Evans, previously known only from Peru, and P. pauxillum Evans, previously known only from Argentina. Finally, P. corvinum Evans, previously known from Argentina and the Atlantic Forest, is recorded here for the first time from Amazon rainforest. Furthermore, 33 new species are described from the region, increasing significantly the number of valid species of this genus in the Brazilian Amazon: P. assai Gomes, Colombo & Somavilla, sp. nov., P. aldenorae Gomes, Colombo & Somavilla, sp. nov., P. arikem Gomes, Colombo & Somavilla, sp. nov., P. bijawu Gomes, Colombo & Somavilla, sp. nov., P. caboclo Gomes, Colombo & Somavilla, sp. nov., P. curumim Gomes, Colombo & Somavilla, sp. nov., P. cunhata Gomes, Colombo & Somavilla, sp. nov., P. divisor Gomes, Colombo & Somavilla, sp. nov., P. ducke Gomes, Colombo & Somavilla, sp. nov., P. esauassum Gomes, Colombo & Somavilla, sp. nov., P. fluvialensis Gomes, Colombo & Somavilla, sp. nov., P. guarana Gomes, Colombo & Somavilla, sp. nov., P. inga Gomes, Colombo & Somavilla, sp. nov., P. inpa Gomes, Colombo & Somavilla, sp. nov., P. juruti Gomes, Colombo & Somavilla, sp. nov., P. maceta Gomes, Colombo & Somavilla, sp. nov., P. mapinguari Gomes, Colombo & Somavilla, sp. nov., P. miudum Gomes, Colombo & Somavilla, sp. nov., P. muiraquita Gomes, Colombo & Somavilla, sp. nov., P. munduruku Gomes, Colombo & Somavilla, sp. nov., P. obidensis Gomes, Colombo & Somavilla, sp. nov., P. pirarucu Gomes, Colombo & Somavilla, sp. nov., P. porangum Gomes, Colombo & Somavilla, sp. nov., P. puku Gomes, Colombo & Somavilla, sp. nov., P. pupunha Gomes, Colombo & Somavilla, sp. nov., P. seringueirae Gomes, Colombo & Somavilla, sp. nov., P. tucuma Gomes, Colombo & Somavilla, sp. nov., P. tucupi Gomes, Colombo & Somavilla, sp. nov., P. uirapuru Gomes, Colombo & Somavilla, sp. nov., P. urucum Gomes, Colombo & Somavilla, sp. nov., P. wemersoni Gomes, Colombo & Somavilla, sp. nov., P. xingu Gomes, Colombo & Somavilla, sp. nov., P. yawanawa Gomes, Colombo & Somavilla, sp. nov. An identification key, discussion of diagnostic morphological characters of the head, median clypeal lobe, and male genitalia, together with distribution maps for all recorded species, are provided.